The utility of prognostic indices, early events, and histological subtypes on predicting outcomes in non‐follicular indolent B‐cell lymphomas. Issue 6 (10th April 2019) - Tracy, Sean I.; Larson, Melissa C.; Feldman, Andrew L.; Maurer, Matthew J.; Novak, Anne J.; Slager, Susan L.; Villasboas, Jose C.; Allmer, Cristine; Habermann, Thomas M.; Farooq, Umar; Syrbu, Sergei; Cerhan, James R.; et al.
Abstract: Indolent B‐cell lymphomas other than follicular lymphoma account for up to 10% of all B‐cell neoplasms. While they typically follow a slowly progressive course, some patients experience rapid progression and early mortality. Prognostic scoring systems have not been adopted, hindering the ability of clinicians or researchers to predict outcomes, or risk‐stratify patients during clinical trials. To address this, we evaluated the utility of existing prognostic indices and novel, early disease‐related outcomes, to predict subsequent long term survival. Baseline characteristics and outcomes data were generated from a longitudinal cohort study that prospectively enrolled 632 patients newly diagnosed with marginal zone lymphoma, lymphoplasmacytic lymphomas, or B‐cell lymphomas not otherwise specified, beginning in 2002. The International Prognostic Index (IPI), Follicular Lymphoma International Prognostic Index (FLIPI), and MALT International prognostic index (MALT‐IPI) demonstrated c‐statistics that ranged from 0.593‐0.612 for event‐free survival (EFS), and 0.683‐0.714 for overall survival (OS). Patients who attained event‐free survival at 12 months (EFS12) experienced similar mortality to the US general population (standardized mortality ratio [SMR] 1.19; 95% CI 0.95‐1.46). Patients who did not attain EFS12 had subsequent worse morality (SMR 3.14 (95% CI 2.05‐4.59). The MALT‐IPI demonstrated utility in predicting subsequent long‐term outcomes among patients with non‐follicular indolent B‐cell lymphomas. This index should be used by clinicians giving guidance to patients at the time of initial diagnosis, and risk stratification during clinical studies. The divergent long‐term outcomes experienced by patients who do or do not attain EFS12 suggest there exists a subset of patients who harbor high‐risk disease. Future research efforts should focus on methods to identify these patients at the time of diagnosis, in order to enable risk‐tailored therapy.